Improved the synthesis of dietary triglycerides by using lipase supported on clay carriers - Pacheco, Bruna Jeanne Soares; Domingues, Otávio [UNESP]; Reina, Mariana Prado [UNESP]; Neto, Alvaro de Babtista [UNESP]; Andrade, Grazielle Santos Silva; de Paula, Ariela Veloso [UNESP] (Wiley, 2022)
Background: In the search for healthier and more functional foods, dietary triglycerides (TAGs) have played a prominent role in the food industry. The objective of this work was to evaluate new clay supports to immobilize lipase from Rhizopus oryzae and use it in the synthesis of TAGs. Main methods and major results: The immobilization of lipase by physical adsorption was carried out, determining the hydrolytic activity, esterification, immobilization yield, thermal stability, and kinetic and thermodynamic parameters. Afterwards, acidolysis was carried out and the product characterized as to composition, acidity index (AI), peroxide index (PI), and analysis of the sn-2 position. The mean hydrolytic activity of free lipase was 23,568.43 ± 559.20 U g−1 and for lipase immobilized in acidified kaolin and diatomite, 1409.04 ± 51.07 and 1235.67 ± 9.56 U g–1; immobilization yield of 23.78% and 20.21% and esterification activity of 1827.99 and 1722.66 U g–1, respectively, maintaining more than 60% of the relative activity after 8 h of incubation at different temperatures. The reaction using the derivative immobilized in acidified diatomite resulted in the degree of incorporation (DI) 41.53% ± 3.99%. Conclusions and implications: From the results, the potential of diatomite and kaolin as support in the immobilization of lipase for the synthesis of dietary TAGs was verified.